1949
DOI: 10.1099/00221287-3-2-255
|View full text |Cite
|
Sign up to set email alerts
|

The Lecithinase of Bacillus cereus and its Comparison with Clostridium welchii  -toxin

Abstract: SUMMARY : Bacillus cereus and B. mycoides produce lecithinases which split lecithin into phosphorylcholine and a diglyceride in the same way as the lecithinase (a-toxin) of Clostridium welchii. These enzymes also possess most of the biological activities associated with Cl. welchii a-toxin, e.g. produce the Nagler reaction and the egg-yolk reaction, lyse red blood cells, and are dermonecrotizing and lethal.The enzymes are activated by Ca and Mg ions, but inhibited by Nay K, NH, ferric and Al ions. Optimal enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1952
1952
1976
1976

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Originally, it was believed that these were due to one toxin, a lecithinase like the alpha-toxin of Clostridium perfringens. 5 T h e studies of Bonventre and Johnson, however, showed that Bacillus ceretis produces significant amounts of different enzymes: penicillinase, phospholipase, hemolysin, and a proteolytic enzyme.2 At least three of these will participate in the pathogenesis in man and animal. A lethal toxin effect was demonstrated i n a number of experimental animals after intravenous, intraperitoneal, and intranasal application.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, it was believed that these were due to one toxin, a lecithinase like the alpha-toxin of Clostridium perfringens. 5 T h e studies of Bonventre and Johnson, however, showed that Bacillus ceretis produces significant amounts of different enzymes: penicillinase, phospholipase, hemolysin, and a proteolytic enzyme.2 At least three of these will participate in the pathogenesis in man and animal. A lethal toxin effect was demonstrated i n a number of experimental animals after intravenous, intraperitoneal, and intranasal application.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolysis of phospholipid by the enzyme may be dependent on the 'combined' state of the substrate in E.Y.B. It is relevant to point out here that lecithinase preparations from Bacillus cereus and Clostridium welchii, which hydrolysed equal amounts of free phospholipid, differed greatly in their ability to hydrolyse lipovitellenin (Chu, 1949). The phospholipase of B. mthracis resembles bacterial lecithinases in being fairly stable to heat and sensitive to surface denaturation.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of lecithinase preparations from Clostridium welchii and Bacillus cereus, both the egg-yolk reaction and the toxicity are inhibited by the same homologous antiserum (MacFarlane, 1955;Chu, 1949 …”
Section: Discussionmentioning
confidence: 99%
“…They believed that neither of these explanations coaild account for the lyso compounds in £. cereus since Chu (1949) reported this organism contained phosphatidase D and not phosphatidase A. They were also unable to detect enol-ether linkages with the plasmal stain of Hack and Ferrans (1959)* In addition to the lyso compounds detected in bacterial lipids by others (Kates si âl», 1962), an additional lyso compound has been detected in the lipids of B. polymyxa.…”
Section: Katesmentioning
confidence: 94%